Relations entre le commerce international et l’emploi; cas du Québec : 1965-1970 - Lafleur, Louis-Robert; Tremblay, Rodrigue (L'Actualité économique)

(untitled) (HEC Montréal, 1973)
AbstractThis article combines the analysis of regional economics, the constant-market-share analysis and the input-output analysis in order to assess the impact of export growth on the main economic variables of a regional economy. The model is first tested for a regional economy by breaking up export growth rates for manufactured products into its various effects. The dynamism of the trade zone to which the regional economy belongs, the production biases on the pattern of trade flows and the cost competitiveness of the economy are then estimated. It is assumed that these estimates reflect the relative importance of the structural and exogenous factors relative to the cyclical and endogenous factors on export performance.The general equilibrium implications of the estimates in terms of direct and indirect employment effects are thus spelled out by the use of available input-output data. The results indicate that Quebec's export performance is not hindered by the geographical pattern of export flows nor by the product-mix of its exports. However, the indicator of cost competitiveness indicates a slight deterioration on foreign markets.